Unstoppable : Kuasa menakjubkan tindakan iman / Nick Vujicic ; Penerjemah, Agnes Cynthia ; Penyunting, Raviyanto Ahmad - NICK Vujicic; AGNES Cynthia; RAVIYANTO Ahmad (Gramedia Pustaka Utama, 2014)
xii, 277 hlm. : ilus. ; 23 cm.